Some Neoperla from Taiwan (Plecoptera: Perlidae). - Sivec, Ignac; Zwick, Peter (Contributions to Entomology = Beiträge zur Entomologie, 1987)
In the fauna of Taiwan, genus Neoperla is represented by several species of the clymene- and der montivaga-group, respectively. The present paper contains redescriptions of known species from type material, and the description of a new species. The following species belong to the clymene-group: Neoperla sauteri Klapalek (lectotype-designated), N. formosa Okamoto, N. cavaleriei (Novas) (lectotype-designated; originally described from the Chinese mainland but present also in Taiwan and very similar to the preseding species), and N. uniformis Banks (lectotype-designated; only the female is known). The presently unknown females of N. sauteri and N. formosana are probably among females provisionally named Neoperla spec. TW A, TW B, TW C und TW D. The montivaga-group is represented by Neoperla signatalis Banks (lectotype-designated), N. klapaleki Banks (presumably the female of the former species), N. costalis (Klapalek) (spec. propr., lectotype-designated) N. taihorinensis (Klapalek) (lectotype-designated) and N. taiwanica Sivec & Zwick sp. n. Genitalia and (or eggs of the species mentioned are illustrated. Nomenclatural Acts cavaleriei (Navás, 1922) (Neoperla), Lectotype described as Ochthopetina cavaleriei costalis Klapálek, 1913 (Neoperla), Lectotype; spec. propr. described as Formosina costalis; previously a syn. of Neoperla hatakeyamae Okoamoto, 1912 sauteri Klapálek, 1912 (Neoperla), Lectotype signatalis Banks, 1937 (Neoperla), Lectotype taihorinensis Klapálek, 1913 (Neoperla), Lectotype described as Formosina taihorinensis taiwanica Sivec & Zwick, 1987 (Neoperla), spec. n. uniformis Banks, 1937 (Neoperla), Lectotype